PENGEMBANGAN MEDIA BELAJAR PUPUH BERBASIS ANDROID - Gusti Ngurah Wira Satryawan; I Gede Mahendra Darmawiguna; I Made Gede Sunarya (Universitas Pendidikan Ganesha, 2014)
Pupuh is one of the four types of songs that exist in Bali. Pupuh is used to express advices, stories of heroism and feelings that usually shown on dramatari which is developedin Bali such as drama gong, arja and Bondres. This Media Belajar Pupuh Berbasis Android is a learning media pupuh with an Android device. This research aims to design andimplement application design Media Belajar Pupuh Berbasis Android.Development of the Media Belajar Pupuh Berbasis Android is using the software development life cycle SDLC (Software Development Life Cycle) with the waterfall model.Features in this application are intended as a learning pupuh for users with an Androiddevice. The features of this application are the theory of pupuh, uger-uger of pupuh, tunings of pupuh, songs of pupuh and recordings of the user.The result of this research is the design and implementation of the Media BelajarPupuh Berbasis Android that has been successfully carried out. The design is done by using a functional model of the UML (Unified Modeling Language). Implemented in Javaprogramming language using the Eclipse editor and ADT (Android Development Tools) plug- ins, and also using AndEngine as additional libraries. The entire functional requirementshave been successfully implemented in accordance with the design.